Design of Website-Based Bugis Waterpark Adventure Tourism Information System Using Agile Method: BugisGo - Vina Annisa Sofyan; Muhammad Iqram; Nur Amalia Ramadhan; Izzaturrahman; Pramudya Asoka Syukur (Sakura Digital Nusantara, 2025)
Bugis Waterpark Adventure in Makassar faces challenges in promotional outreach and information accessibility due to the absence of a professionally designed web-based information system. This research aims to design and develop a web-based tourist information system, BugisGo, to improve accessibility and visitor experience. The system was developed using the Agile method, which involves the stages of system planning, requirements analysis, system design, implementation, and iterative testing. BugisGo successfully implemented key features such as online ticket booking, payment system, and visitor feedback. Black-box and white-box testing showed that the system functions properly and securely. The Agile development process allows for flexibility and continuous improvement based on user feedback, increasing visitor satisfaction and operational efficiency. The BugisGo system successfully improved accessibility and visitor experience, but further research is needed for performance testing under high load conditions and mobile application integration.